Progressive subcutaneous emphysema of unknown origin: a surgical dilemma. Issue 4 (4th July 2019) - De Roeck, Lynn; Van Assche, Lauranne; Verhoeven, Veronique; Vrints, Ina; Van Thielen, Jana; Tondu, Thierry; Thiessen, Filip
Abstract: Objective: Subcutaneous emphysema can be an alarming sign of a necrotizing soft tissue infection. However, non-infectious etiologies exist that can be treated conservatively. This case report describes a subcutaneous emphysema of unknown origin and highlights the importance of distinguishing these clinical entities. Methods: We present a 17-year old female with pain and subcutaneous emphysema of the left arm. There were no systemic symptoms. Inflammatory parameters were slightly elevated. Computed tomography (CT) scan of the chest excluded intrathoracic abnormalities. Despite antibiotic treatment, the pain increased and the emphysema extended. Necrotizing fasciitis was feared. A surgical exploration was performed and hyperbaric oxygen therapy was started. Results: Intraoperatively, puncture marks were identified on the left arm. Air noticeably escaped, but normal, unaffected tissues were identified and microbiological cultures remained negative. We observed a good clinical evolution. Conclusion: The lack of apparent causes, the unexplained puncture marks and psychiatric comorbidity suggests the possibility of subcutaneous emphysema due to factitious manipulations. Patients with subcutaneous emphysema who remain clinically stable, have minimal pain and no significant inflammatory changes could be treated conservatively. Close clinical monitoring is essential to avoid delayed intervention in case of a necrotizing soft tissue infection.